Health Beliefs Model and Self Efficacy among Type II Diabetic Patients - أحمد, سمر; طويل , علاء; اصبيره , ولاء (Latakia University Journal -Medical Sciences Series, 2022)
Diabetes is not a purely medical problem، because the expected outcomes of the disease depends on the patient's participation، behavior and beliefs about the disease، based on the idea that good health is the product of a cumulative personal achievement. Therefore، the current study aimed to evaluate the model of health beliefs and self-efficacy among patients with type II diabetes in the city of Lattakia، using the descriptive exploratory approach. Data were collected from 50 patients of both sexes in the eighth health center، they were selected by appropriate non-random sampling method، and data were collected using diabetes health belief model and diabetes self-efficacy scale. The results showed that the largest proportion of patients (46%) over the age of 60 years، about half (48%) of them had the disease more than 10 years ago. The study also showed that patients had a negative perception of susceptibility to disease complications (7.17 ± 2.7) and barriers to initiating healthy behaviors (24.39 ± 7.1)، with a positive perception of disease severity and complications (10.53 ± 5.9) and positive cues of starting work (34.1 ± 3.5) on changing Their unhealthy behaviors. Also (48%) of the patients had a moderate self- efficiency in their ability to perform healthy behaviors، with statistically significant differences in their health beliefs related to age and educational level (P≤0.05)، and self-efficacy increased with the presence of a family history of the disease. Therefore، the current study recommends that education and awareness programs for diabetes patients be designed according to their needs، with a focus on raising the level of self-efficacy and removing barriers to implementing the health behaviors required to prevent the aggravation and complications of the disease.